A report on the status of coaches in Canada. A Summary of the findings - Reade, I.; Rodgers, W.; Holt, N.; Dunn, J.; Hall, N.; Stolp, S.; Jones, L.; Smith, J.; Baker, T. (2009)
The working conditions for Canada`s high performance coaches are less than ideal given the significant time commitment, the heavy workload required, and the salaries received by coaches of the country`s top athletes. These challenges are a central portion of the findings of a study on the Status of Coaches in Canada released this morning by the Coaching Association of Canada (CAC). The report`s results were discussed at a news conference attended by Minister of State (Sport) Gary Lunn, CAC Chief Executive Officer John Bales, and Own the Podium Executive Director and two-time Olympic gold medallist Alex Baumann. "This new study will help us to identify areas where we can work together with Canadian coaches to help our athletes excel from the playground to the podium," said Minister of State Lunn. "Our Government will continue to work with our partners to ensure our athletes have the resources and support they need to succeed." Unreasonable workload, lack of job security, retention, and succession issues were among key findings highlighted by the study. Analysis of these findings will provide an opportunity for sport organizations, governments, and institutions to identify how to better address these issues. "Coaching is a profession in transition, as this study demonstrates by profiling a diverse group of high performance coaches in a wide range of working conditions," said John Bales, CAC Chief Executive Officer. "It highlights the need to support our Canadian coaches in their work, and give them the resources to be able to perform their jobs to the best of their abilities and in turn have the best possible impact on their athletes." The study was undertaken to improve understanding of the current working conditions of Canadian coaches of high performance athletes. It provides a thorough investigation of their job status, their levels of satisfaction with different aspects of their work, and their feelings in general about being coaches. "This study highlights the need to support high performance coaches to focus on the job of coaching and not be distracted by administrative responsibilities or a lack of security in their positions," said Alex Baumann, Executive Director of Own the Podium and two-time Olympic gold medallist. "Own the Podium places a high priority on technical leadership and the important role of the coach. A better system for high performance coaches in Canada will ultimately lead to more podium performances for our country's top athletes." Initiatives to address the gaps brought to light by this study have already been put in motion. A working group consisting of representatives of Sport Canada, CAC, Own the Podium, Coaches of Canada, national sport organizations, and the study`s principal researcher, will be created. The working group will analyze, prioritize, and develop implementation solutions. Standardized tools will also be considered as part of a plan to promote coaching needs at all levels of the sport system. "The study on the Status of Coaches in Canada will serve as a starting point in the effort to bring appropriate recognition, support and compensation to Canada`s high performance and professional coaches", said Wayne Parro, Coaches of Canada Executive Director. "It is clear from the data generated by the study that many areas related to high performance coaching require attention, but having this information in hand now gives the sport community a framework in which to work towards improvement." "The Status of Coaches in Canada report highlights challenges experienced by high performance coaches, and it is important that when we look to improve their working conditions that we also consider how we can improve the situation for developmental coaches," said Ken Bagnell, President of the Canadian Sport Centre Atlantic. "Provincial and territorial initiatives are crucial in helping to create better working conditions at the developmental level, which in turn would result in an increased stability for high performance coaches and the athletes with whom they work." About the study on the Status of Coaches in Canada The study was conducted by the Coaching Research Group at the Faculty of Physical Education and Recreation of the University of Alberta, made possible through the financial support of Sport Canada, and monitored and reviewed by the Coaching Association of Canada`s Project Steering Committee, which included representatives from Sport Canada, Own the Podium, Coaches of Canada, and CAC. This research was conducted with 819 coaches from March to August 2008, and with 94 employers in the summer and fall of 2008. Coaches respondents were from universities, colleges, national and provincial teams, and Canada Games levels. Employers who participated were direct supervisor or main employer of coaches within national sport organizations, colleges, and universities.